DETERMINAN BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN BAKSO BOEDJANGAN DI KOTA BOGOR - Angga Putri Ekanova Nurlaela; Ranti Putri Pratiwi (Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of marketing mix variables on consumer satisfaction of Bakso Boedjangan Bogor. This type of research is research quantitative. The sampling technique used accidental sampling technique with a total sample of 96 consumers who consumed Bakso Boedjangan Bogor. The regression equation in this study is multiple linear regression which is used to test the effect of the independent variables on the dependent variable. The results of the goodness of fit test show that the marketing mix is an explanatory variable for consumer satisfaction. The results of hypothesis testing show that product variables have no significant effect on customer satisfaction, prices have a significant effect on customer satisfaction. Location has a significant effect on consumer satisfaction. Promotion has a significant effect on consumer satisfaction. The variables that have a dominant influence on customer satisfaction are price, location and promotion.